Analysis of the Tax Reform Act of 1969/Working with the Revenue Code –1971. - Crumbley, D. Larry; Sterling, Robert R. (The Accounting Review, 1971)
Abstract Reviews two books on taxation. "Analysis of the Tax Reform Act of 1969," edited by Gilbert Simonetti, Jr. and Harry Z. Garian; "Working With the Revenue Code–1971," by Don J. Summa.